Alkaline developing resin composition, photocurable dry film thereof, cured product thereof, and printed wiring board formed using the same

By using a specific proportion of the alkaline developing resin composition of soft composite glass powder and heavy calcium carbonate filler in the pad registration layer of the copper foil circuit board, the problem of cracking and insufficient adhesion in the hot and cold cycles is solved, and high adhesion and hot and cold impact resistance are improved.

JP2025503074AActive Publication Date: 2025-01-30TAIYO INK SUZHOU
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024543265
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-12-27
Publication Date
2025-01-30
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

In the prior art, the pad registration layer of the copper foil circuit board is prone to cracking during the hot and cold cycle process and has the problem of insufficient adhesion. Especially when used in high-reliability electronic equipment such as automobiles, trains, ships and aircraft, it is impossible to meet the high hot and cold impact resistance and adhesion requirements at the same time.

Method used

An alkaline developing resin composition containing a specific proportion of soft composite glass powder and heavy calcium carbonate as fillers is used to form a pad registration layer through photopolymerization, and the resin composition is adjusted to improve adhesion and hot and cold impact resistance.

Benefits of technology

The high adhesion and high impact resistance of the pad registration layer under hot and cold cycle conditions are achieved, ensuring the reliability and stability of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503074000010
    Figure 2025503074000010
  • Figure 2025503074000011
    Figure 2025503074000011
  • Figure 2025503074000012
    Figure 2025503074000012
Patent Text Reader

Abstract

The present invention provides an alkaline developable resin composition capable of forming a solder resist layer having excellent adhesion and thermal shock resistance, a photocurable dry film thereof, a cured product thereof, and a printed wiring board formed using them. The alkaline developable resin composition contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) glass powder, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, the (E) inorganic filler containing talc, and the (C) glass powder containing, by weight %, SiO 2 : 60~65%, Fe 2 O 3 : 0.01~0.02%, Al 2 O 3 :14~20%, CaO:6~9%, MgO:1~2%, B 2 O 3 The (C) glass powder contains 8 to 12% of glass, and the Mohs hardness of the glass powder is less than 6.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alkaline developable resin composition suitable for forming a solder resist layer of a printed wiring board, a photocurable dry film thereof, and a cured product thereof, and in particular to an alkaline developable resin composition capable of forming a solder resist layer having excellent adhesion and thermal shock resistance, a photocurable dry film thereof, and a cured product thereof, and a printed wiring board. [Background technology]

[0002] At present, for the formation of solder resist layers (solder resists) for some consumer printed wiring boards and most industrial printed wiring boards, an alkaline development type solder resist agent is used, which is exposed to ultraviolet light, developed to form a pattern, and completely cured (mainly cured) by heat and / or light irradiation. Also, for semiconductor devices used in vehicles such as automobiles, trains, ships, and aircraft, there is a tendency for solder resist agents for high reliability electronic materials to be used as solder resist agents for printed wiring boards. However, general alkaline development type solder resists usually have poor crack resistance during thermal cycles and poor reliability against changes in environmental temperature due to thermal expansion and other reasons. In addition, the solder resist layer is required to have excellent adhesion in terms of protecting the copper circuit and aesthetics. Although cracks can be improved by selecting talc as a filler, the adhesion is poor. In addition, when talc and silica are used as fillers, the requirements for thermal shock resistance of solder resists for automotive use may be met, but the adhesion is still insufficient.

[0003] For example, the photocurable solder resist of Patent Document 1 uses silica, barium sulfate, and talc as fillers. The curable resin composition for solder resist layer of Patent Document 2 contains a carboxyl group-containing resin, a thermosetting component, a flame retardant, and an ion trapping agent, and the ion trapping agent is a mixture of a hydrotalcite-based ion trapping agent and an ion trapping agent other than hydrotalcite-based ion trapping agent, and aluminum hydroxide is used as an inorganic filler. The curable resin composition of Patent Document 3 is used as a permanent mask for printed wiring boards, and contains a resin containing an ethylenically unsaturated group and a carboxyl group in the molecule, a photopolymerization initiator, a photopolymerizable monomer, titanium oxide surface-treated with alumina, barium sulfate and / or talc, and an organic solvent. Patent Document 4 describes that the filler of the ultraviolet light-curable liquid photosensitive solder resist flexible ink is barium sulfate, talc, or silica. [Prior art documents] [Patent documents]

[0004] Patent document 1: CN114716868A Patent document 2: CN108137791A Patent document 3: CN101798432A Patent document 4: CN106380929A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide an alkaline developable resin composition capable of forming a solder resist layer having excellent adhesion and thermal shock resistance, a photocurable dry film thereof, a cured product thereof, and a printed wiring board. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve the above problems, and have found that the type of filler has a significant effect on thermal shock resistance. An alkaline developing resin composition containing (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) glass powder, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, the inorganic filler containing talc, the glass powder containing, by weight, SiO2: 60-65%, Fe2O3: 0.01-0.02%, Al2O3: 14-20%, CaO: 6-9%, MgO: 1-2%, and B2O3: 8-12%, and the Mohs hardness of the glass powder (C) is less than 6.5, has solved the above problems, and has completed the present invention.

[0007] That is, the alkaline developable resin composition of the present invention contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) glass powder, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, wherein the (E) inorganic filler contains talc, the (C) glass powder contains, by weight, 60 to 65% SiO2, 0.01 to 0.02% Fe2O3, 14 to 20% Al2O3, 6 to 9% CaO, 1 to 2% MgO, and 8 to 12% B2O3, and the (C) glass powder has a Mohs hardness of less than 6.5.

[0008] It is also preferred to contain (F) other additives other than (B) the photopolymerization initiator and (C) the glass powder.

[0009] It is also preferable that the composition contains an epoxy resin (G).

[0010] It is also preferred that the solvent contains an organic solvent (H).

[0011] The photocurable dry film of the present invention is characterized in that it is obtained by applying the alkaline developing resin composition to a carrier film and drying it.

[0012] The cured product of the present invention is characterized in that it is obtained by applying the alkaline developable resin composition to copper and drying the coating film, or by applying the alkaline developable resin composition to a carrier film, drying the resulting photocurable dry film, and laminating the resulting coating film on copper, followed by photocuring the resulting coating film.

[0013] The printed wiring board of the present invention is characterized in that it is obtained by applying the alkaline developable resin composition to a substrate having a copper circuit and drying the composition to obtain a coating film, or by applying the alkaline developable resin composition to a carrier film, drying the composition, and laminating the resulting photocurable dry film onto a substrate having a copper circuit to obtain a coating film, followed by photocuring and then thermal curing the coating film.

[0014] The alkaline developable resin composition of the present invention contains (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) glass powder, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, wherein the (E) inorganic filler contains talc, the (C) glass powder contains, by weight, 60 to 65% SiO2, 0.01 to 0.02% Fe2O3, 14 to 20% Al2O3, 6 to 9% CaO, 1 to 2% MgO, and 8 to 12% B2O3, and is most significantly characterized in that the (C) glass powder has a Mohs hardness of less than 6.5.

[0015] Based on the characteristic configuration of the present invention, by using soft composite glass powder and talc in combination and adjusting the compounding ratio of the two, it is possible to improve adhesion while maintaining excellent thermal shock resistance.

[0016] In response to this, in the conventional technology, the requirement for thermal shock resistance of the solder resist can be met by using talc and barium sulfate in combination as a filler, but this leads to poor adhesion (for example, Patent Document 1, etc.).

[0017] As described above, the inventors of the present invention conducted extensive research and found that talc, as a filler, has good flexibility and excellent crack resistance in a Temperature Cycle Test (hereinafter sometimes abbreviated as "TCT test"), but the adhesive strength deteriorates as the amount used increases. Glass powder, particularly soft composite glass powder, can provide excellent adhesive strength as a filler, but its thermal shock resistance is insufficient. By using talc and glass powder in combination as a filler, it is possible to simultaneously maintain excellent thermal shock resistance and adhesive strength, thereby achieving the above-mentioned object of the present invention. Effect of the Invention

[0018] As described above, according to the present invention, it is possible to provide an alkaline developable resin composition capable of forming a solder resist layer having excellent adhesion and thermal shock resistance, a photocurable dry film thereof, a cured product thereof, and a printed wiring board. [Brief description of the drawings]

[0019] [Figure 1] 1 is a photograph showing that cracks were generated in a solder resist film for evaluating thermal shock resistance in an example. [Diagram 2] FIG. 2 is a photograph showing that no cracks were generated in the solder resist film used to evaluate thermal shock resistance in the example. [Diagram 3] FIG. 2 is an image of a dolly used to evaluate adhesion in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Each of the components of the alkaline developing resin composition of the present invention will be described below.

[0021] The alkaline developable resin composition of the present invention contains (C) glass powder and (E) inorganic filler. The (E) inorganic filler is characterized by containing talc as an essential component. Therefore, first, the (C) glass powder and the (E) inorganic filler will be described.

[0022] (C) Glass powder The glass powder (C) used in the alkaline developing resin composition of the present invention is a powdered amorphous inorganic material in a glassy state, mainly composed of silica, and is typically formed by high-temperature sintering using inorganic minerals as the main raw material.

[0023] The glass powder (C) used in the alkaline developing resin composition of the present invention is preferably a soft composite glass powder, because it is more advantageous in achieving the object of the present invention. The glass powder (C) may be a glass powder that has not been surface-treated, or may be a surface-treated glass powder.

[0024] The soft composite glass powder typically has a composition of SiO2: 60-65%, Fe2O3: 0.01-0.02%, Al2O3: 14-20%, CaO: 6-9%, MgO: 1-2%, and B2O3: 8-12%, preferably SiO2: 61-64%, Fe2O3: 0.012-0.019%, Al2O3: 15-19%, CaO: 6.5-8.5%, MgO: 1.1-1.8%, and B2O3: 9-11%, and more preferably SiO2: 62-63%, Fe2O3: 0.014-0.018%, Al2O3: 16-18%, CaO: 7-8%, MgO: 1.2-1.6%, and B2O3: 9.5-10.5%.

[0025] The soft composite glass powder has a Mohs hardness of less than 6.5, preferably in the range of 4.8 to 6.2, and more preferably in the range of 5 to 6.

[0026] The present inventors have found that, in order to achieve both thermal shock resistance and adhesive strength of the solder resist layer, by using talc as a filler and blending (C) glass powder, it is possible to remarkably improve adhesive strength while maintaining excellent thermal shock resistance. In this case, the blending ratio of the two is appropriate, that is, talc:glass powder is 90:10 to 10:90 by weight, preferably 80:20 to 20:80, more preferably 75:25 to 25:75, and even more preferably 70:30 to 30:70. In this way, an alkaline development type resin composition capable of realizing a solder resist layer excellent in both thermal shock resistance and adhesive strength can be obtained.

[0027] The blending ratio of the (C) glass powder is suitably 10 to 90 parts by weight relative to 100 parts by weight (solid content equivalent) of the (A) vinyl ester resin, preferably 20 to 80 parts by weight, more preferably 30 to 70 parts by weight, and further preferably 40 to 60 parts by weight. If the amount of the (C) glass powder used is within the above range, it is possible to obtain excellent thermal shock resistance and ensure improved adhesion. If the amount exceeds the above range, the properties as a solder resist agent are reduced, which is not preferable.

[0028] Commercially available soft composite glass powders include K10 (manufactured by Suzhou Jin Yi New Material Co., Ltd.) and G2C (manufactured by Shanghai Sibelco Mining Co., Ltd.).

[0029] (E) Inorganic filler In the alkaline-developable resin composition of the present invention, the talc used as the inorganic filler (E) is used to improve thermal shock resistance, and the inorganic filler (E) does not include the above-mentioned glass powder (C), in particular the soft composite glass powder.

[0030] The talc may be any one of magnesium carbonate, serpentine, silica / silica-alumina, and magnesium deposits, and may be any one of so-called silicate minerals, and may be in the form of a lump or fine powder. Surface treatment may or may not be performed. The average particle size of the talc is suitably 1.0 to 20.0 μm, more preferably 2.0 to 10 μm, and even more preferably 3.0 to 8.0 μm. Examples of commercially available products include HD25 manufactured by Talc Mining Co., Ltd., Pingdu City, Shandong Province, and LMP-100 manufactured by Fuji Talc Industry Co., Ltd.

[0031] The amount of talc is suitably 10 to 90 parts by weight, preferably 20 to 80 parts by weight, and more preferably 30 to 70 parts by weight, per 100 parts by weight of the (A) vinyl ester resin (solid content equivalent). If it is within the above range, adhesion can be improved while excellent thermal shock resistance is ensured.

[0032] As long as the object of the present invention is not impaired, a filler other than talc and the above-mentioned (C) glass powder, such as silica, may be blended. The silica may be either amorphous or crystalline, or may be a mixture thereof. Particularly preferred is amorphous (fused) silica. Surface treatment may or may not be performed. The silica typically has a Mohs hardness of 6.5 or more. The average particle size of the silica is suitably 0.1 to 10.0 μm, more preferably 1.0 to 8.0 μm, and even more preferably 2.0 to 6.0 μm. Commercially available products of the silica include CS1002 and CS1002A manufactured by Jiangsu NOVORAY New Materials Co., Ltd., A-8 manufactured by Sibelco Co., Ltd., SE-40 manufactured by Tokuyama Co., Ltd., MSV25G manufactured by Tatsumori Co., Ltd., MLV-2114 manufactured by Tatsumori Co., Ltd., SO-E5 manufactured by ADMATECHS, SO-E2 manufactured by ADMATECHS, and the like.

[0033] (A) Vinyl ester resin

[0034] As the vinyl ester resin (A) in the photocurable thermosetting resin composition of the present invention, a known resin having an ethylenically unsaturated double bond in the molecule can be used from the viewpoint of photocurability and development resistance. In addition, in order to impart alkaline developability, a carboxyl group-containing resin having an ethylenically unsaturated double bond in the molecule is particularly preferred. In addition, the unsaturated double bond is more preferably derived from acrylic acid or methacrylic acid or a derivative thereof. As the vinyl ester resin (A), a resin using an epoxy resin as a starting material, a polyurethane resin having a urethane skeleton, a copolymer resin having a copolymer structure of an unsaturated carboxylic acid, or a resin using a phenol compound as a starting material is preferred. Specific examples of the vinyl ester resin (A) are shown below.

[0035] (1) A vinyl ester resin obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with one or more other compounds having an unsaturated double bond. (2) Photosensitive vinyl ester resins obtained by adding an ethylenically unsaturated group as a side group to a copolymer of an unsaturated carboxylic acid such as (meth)acrylic acid and one or more other compounds having an unsaturated double bond, using a compound having an epoxy group and an unsaturated double bond, such as glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, or (meth)acrylic acid chloride, etc.; (3) A photosensitive vinyl ester resin obtained by reacting a copolymer of a compound having an epoxy group and an unsaturated double bond, such as glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, with an unsaturated carboxylic acid, such as (meth)acrylic acid, and then reacting the resulting secondary hydroxyl group with a polybasic acid anhydride. (4) A photosensitive vinyl ester resin obtained by reacting a copolymer of an acid anhydride having an unsaturated double bond, such as maleic anhydride, and another compound having an unsaturated double bond with a compound having a hydroxyl group and an unsaturated double bond, such as 2-hydroxyethyl (meth)acrylate. (5) A vinyl ester resin obtained by reacting a polyfunctional epoxy compound with an unsaturated monocarboxylic acid and reacting the resulting hydroxyl group with a saturated or unsaturated polybasic acid anhydride. (6) A vinyl ester resin containing hydroxyl groups and carboxyl groups, which is obtained by reacting a hydroxyl group-containing polymer such as a polyvinyl alcohol derivative with a saturated or unsaturated polybasic acid anhydride, and then reacting the resulting carboxylic acid with a compound having an epoxy group and an unsaturated double bond in one molecule. (7) A vinyl ester resin obtained by reacting a reaction product of a polyfunctional epoxy compound, an unsaturated monocarboxylic acid, and a compound having in one molecule at least one alcoholic hydroxyl group and one reactive group other than the alcoholic hydroxyl group that reacts with an epoxy group, with a saturated or unsaturated polybasic acid anhydride. (8) A vinyl ester resin obtained by reacting a polyfunctional oxetane compound having at least two oxetane rings in one molecule with an unsaturated monocarboxylic acid, and reacting a primary hydroxyl group in the resulting modified oxetane resin with a saturated or unsaturated polybasic acid anhydride; and (9) A vinyl ester resin obtained by reacting a polyfunctional epoxy resin with an unsaturated monocarboxylic acid, followed by reaction with a polybasic acid anhydride to obtain a carboxyl group-containing resin, and then reacting the resulting resin with a compound having one oxirane ring and one or more ethylenically unsaturated groups in the molecule; (10) A vinyl ester resin obtained by reacting an unsaturated monocarboxylic acid with a bifunctional epoxy compound and then reacting the resulting hydroxyl group with a saturated or unsaturated polybasic acid anhydride.

[0036] Among these examples, the vinyl ester resins (2), (5), (7) and (9) are particularly preferred.

[0037] In this specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and mixtures thereof, and the same applies to other similar expressions hereinafter.

[0038] The vinyl ester resin (A) described above has a plurality of free carboxyl groups in the side chains of the main chain polymer, and therefore can be developed using a dilute aqueous alkali solution.

[0039] The acid value of the vinyl ester resin (A) is preferably in the range of 40 to 200 mgKOH / g, more preferably in the range of 45 to 120 mgKOH / g. If the acid value of the vinyl ester resin (A) is less than 40 mgKOH / g, alkaline development becomes difficult, while if it exceeds 200 mgKOH / g, dissolution of the exposed area by the developer proceeds, resulting in lines becoming thinner than necessary, or in some cases, the exposed area and the unexposed area are dissolved and peeled off by the developer indistinguishably, making it difficult to draw a normal resist pattern, which is undesirable.

[0040] The weight-average molecular weight of the vinyl ester resin (A) varies depending on the resin skeleton, but is generally in the range of 2,000 to 150,000, and more preferably 5,000 to 100,000. If the weight-average molecular weight is less than 2,000, the tack-free performance after application to a substrate and drying may be poor, and the moisture resistance of the coating film after exposure may be poor, film loss may occur during development, and resolution may be significantly poor. On the other hand, if the weight-average molecular weight exceeds 150,000, the developability may be significantly poor and storage stability may be poor.

[0041] The amount of the vinyl ester resin (A) is desirably in the range of 20 to 60 mass % of the total composition, and preferably 25 to 50 mass %, calculated as solid content. If the amount of the vinyl ester resin (A) is less than the above range, the strength of the coating film is reduced, which is not preferable. On the other hand, if the amount is more than the above range, the viscosity of the composition increases or the coatability is reduced, which is not preferable.

[0042] (B) Photopolymerization initiator The photopolymerization initiator used in the alkaline developing type resin composition of the present invention is not particularly limited as long as it is a photopolymerization initiator generally used in alkaline developing type resin compositions.

[0043] As the photopolymerization initiator, known ones can be used, including benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, and 4-(1-t-butyldioxy-1-methylethyl)acetophenone; anthraquinones such as 2-methylanthraquinone, 2-amylanthraquinone, 2-t-butylanthraquinone, and 1-chloroanthraquinone. thioxanthone, such as isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, and 2,4-chlorothioxanthone; ketals, such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenone, 4-(1-t-butyldioxy-1-methylethyl)benzophenone, and 3,3',4,4'-tetrakis(t-butyldioxycarbonyl)benzophenone; and oxoanthracene.

[0044] In addition, as the photopolymerization initiator, an oxime ester-based photopolymerization initiator having an oxime ester group, an alkylphenone-based photopolymerization initiator, an α-aminoacetophenone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a titanocene-based photopolymerization initiator, a phosphate-based photopolymerization initiator, or the like can also be used.

[0045] Commercially available oxime ester photopolymerization initiators include Irgacure OXE01 and Irgacure OXE02 manufactured by BASF Japan, and N-1919 and NCI-831 manufactured by ADEKA CORPORATION. A photopolymerization initiator having two oxime ester groups in the molecule can be suitably used, and specifically, an oxime ester compound having a carbazole structure can be mentioned.

[0046] Commercially available alkylphenone photopolymerization initiators include α-hydroxyalkylphenones such as Omnirad 184, Omnirad 1173, Omnirad 2959, and Omnirad 127 manufactured by IGM Resins BV.

[0047] Specific examples of the α-aminoacetophenone-based photopolymerization initiator include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone, etc. Commercially available products include Omnirad 907, Omnirad 369, Omnirad 379, etc. manufactured by IGM Resins BV.

[0048] Specific examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, trifunctional or higher acylphosphine photopolymerization initiators, etc. The trifunctional or higher acylphosphine photopolymerization initiator may be a photopolymerization initiator having three or more acylphosphine oxide skeletons in one molecule, and can be represented by the following formula (I). JPEG2025503074000001.jpg27169In formula, A's are each independently a single bond, O, S or NR 3 represents G is a multifunctional compound (core) G-(AH) m+n where AH represents an alcohol group, an amino group, or a thiol group, m and n are both integers, and m+n is an integer between 3 and 10; m is an integer between 3 and 8; R1 and R2, independently of one another, each represent a C1-C aryl group that is uninterrupted or interrupted by one or more oxygen and / or sulfur atoms and / or one or more substituted or unsubstituted imino groups. 18 Alkyl groups, C6-C 12 Aryl groups and C5-C 12 or R1 and R2 are each independently a 5- to 6-membered heterocyclic group containing oxygen and / or nitrogen and / or sulfur atoms, which may be substituted with an aryl group, an alkyl group, an aryloxy group, an alkoxy group, a heteroatom and / or a heterocyclic group; R2 may be R1-(C=O)-; Y is O or S; R3 is hydrogen or a C1 to C4 alkyl group.

[0049] Here, the photopolymerization initiator represented by formula (I) does not contain a photocurable ethylenically unsaturated group.

[0050] Preferably, in formula (I), m+n is an integer between 3 and 8, more preferably an integer between 3 and 6. For example, in formula I, m is an integer between 3 and 6, more preferably an integer between 3 and 5.

[0051] In formula (I), when A is oxygen, G-(AH) m+n is a polyhydroxy compound selected from the group consisting of monomeric polyols, oligomeric polyols, and polymeric polyols, and mixtures thereof. When A is sulfur, G-(AH) m+n is a polythiol compound. In formula (I), when A is nitrogen, G-(AH) m+n is a linear or branched polyamine. When A is a mixture of oxygen and / or nitrogen and / or sulfur, G-(AH) m+n is a compound containing different functional groups, for example a compound containing an amino group and a hydroxy group. Residue G- suitable for carrying out the present invention does not contain a photocurable ethylenically unsaturated group. When A is a single bond, G- is the G-(AH) exemplified above. m+nIt is a residue obtained by removing a hydroxy group and / or an amino group and / or a mercapto group from the above.

[0052] Preferably, G-(AH) m+n The number average molecular weight is 1,500 or less, more preferably 800 or less, and even more preferably 500 or less.

[0053] When n is not 0, the compound of formula (I) has alcoholic free groups and / or amino groups and / or mercapto groups.

[0054] Representative trifunctional or higher acylphosphine photopolymerization initiators included in formula (I) are shown in Table 1. Among them, PI-3, PI-4, PI-10, PI-11, PI-12, PI-14, and PI-17 are particularly preferred. By including such trifunctional or higher acylphosphine photopolymerization initiators, outgassing is suppressed, and a cured product with superior insulation reliability can be obtained.

[0055] [Table 1] JPEG2025503074000003.jpg225169JPEG2025503074000004.jpg226170JPEG2025503074000005.jpg183169 JPEG2025503074000006.jpg183170JPEG2025503074000007.jpg218170JPEG2025503074000008.jpg109168

[0056] Such tri- or higher functional acylphosphine photopolymerization initiators can be produced by the method described in Japanese Patent No. 6,599,446, for example.

[0057] As commercially available acylphosphine oxide photopolymerization initiators, Omnirad TPO manufactured by IGM Resins, Omnirad 819 and Omnipol TP manufactured by IGM Resins BV, and the like can be used.

[0058] Specific examples of the titanocene photopolymerization initiator include bis(cyclopentadienyl)(diphenyl)titanium(IV), bis(cyclopentadienyl)titanium(IV) dichloride, bis(cyclopentadienyl)-bis(2,3,4,5,6-pentafluorophenyl)titanium(IV), bis(cyclopentadienyl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium(IV), etc. Commercially available products include Omnirad 784 manufactured by IGM Resins BV.

[0059] The blending ratio of these photopolymerization initiators (B) is suitably 0.01 to 30 parts by weight, preferably 5 to 25 parts by weight, and more preferably 10 to 20 parts by weight, relative to 100 parts by weight (solid content equivalent) of the vinyl ester resin (A). If the amount of the photopolymerization initiator used is less than the above range, the photocurability of the composition deteriorates, whereas if it is too much, the properties as a solder resist agent deteriorate, which is not preferable.

[0060] In this specification, the term "polymer" is a general term for homopolymers, copolymers and mixtures thereof, and the same applies to other similar expressions.

[0061] (D) Compounds having two or more ethylenically unsaturated groups in one molecule The compound (D) having two or more ethylenically unsaturated groups per molecule used in the alkaline developing resin composition of the present invention is a compound that can be photocured by irradiation with active energy rays to make the vinyl ester resin (A) insoluble in an alkaline aqueous solution or to help make the vinyl ester resin insoluble in an alkaline aqueous solution. Specific examples of such compounds include: Hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate, Monoacrylates or diacrylates of glycols such as ethylene glycol, methoxytetraethylene glycol, polyethylene glycol, and propylene glycol; Acrylamides such as N,N-dimethylacrylamide, N-methylolacrylamide, and N,N-dimethylaminopropylacrylamide; Aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; Polyols such as hexanediol, trimethylolpropane, pentaerythritol, dipentaerythritol, tris(2-hydroxyethyl) isocyanurate, etc., or polyhydric acrylates such as ethylene oxide adducts or propylene oxide adducts thereof, acrylates such as phenoxy acrylate, bisphenol A diacrylate, and ethylene oxide or propylene oxide adducts of these phenols; acrylates of glycidyl ethers such as glycerin diglycidyl ether, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and melamine acrylate, and at least one of the methacrylates corresponding to the above acrylates.

[0062] Further examples include epoxy acrylate resins obtained by reacting acrylic acid with a multifunctional epoxy resin such as a cresol novolac epoxy resin, and epoxy urethane acrylate compounds obtained by reacting a hydroxyl group of this epoxy acrylate resin with a half urethane compound of a hydroxyacrylate such as pentaerythritol triacrylate and a diisocyanate such as isophorone diisocyanate.

[0063] The amount of compound (D) having two or more ethylenically unsaturated groups in one molecule is preferably 5 to 100 parts by weight, more preferably 10 to 70 parts by weight, relative to 100 parts by weight of the vinyl ester resin (A) (based on solid content). If the amount is less than 5 parts by weight relative to 100 parts by weight of the vinyl ester resin (A), the photocurability of the resulting alkaline development type resin composition decreases, making it difficult to form a pattern by alkaline development after irradiation with active energy rays, which is not preferred. On the other hand, if the amount exceeds 100 parts by weight, the solubility in an alkaline aqueous solution decreases, making the cured coating film brittle, which is not preferred.

[0064] (F) Other additives As described above, the other additives in the present invention refer to additives other than (B) the photopolymerization initiator and (C) the glass powder.

[0065] Examples of such additives include known and commonly used colorants such as phthalocyanine blue, phthalocyanine green, iodine green, disazo yellow, crystal violet, titanium oxide, carbon black, and acid black; known and commonly used thermal polymerization inhibitors such as hydroquinone, hydroquinone monomethyl ether, tert-butylcatechol, pyrogallol, and phenothiazine; known and commonly used thickeners such as finely divided silica, organic bentonite, and montmorillonite; at least one of silicone-based, fluorine-based, and polymer-based defoamers and leveling agents; adhesion imparting agents such as imidazole-based, thiazole-based, and triazole-based agents; silane coupling agents; phenol-based, phosphorus-based, and sulfur-based antioxidants; hindered amine-based light stabilizers; and dispersing agents.

[0066] The blending ratio of such (F) other additives is suitably 0.01% by weight or more and 20% by weight or less of the total amount of the alkaline developing resin composition. If it is less than 0.01% by weight, the effect is not sufficiently obtained, while if it exceeds 20% by weight, the printability and hardness of the alkaline developing resin composition are deteriorated, which is not preferable.

[0067] (G) Epoxy resin In order to impart heat resistance, it is preferable to blend an epoxy resin having at least two epoxy groups in the molecule, that is, a polyfunctional epoxy resin (G), in the alkaline developing resin composition used in the present invention.

[0068] Commercially available products include bisphenol A type epoxy resins such as jER828, jER834, jER1001, and jER1004 manufactured by Mitsubishi Chemical Corporation, EPICLON 840, 850, 850S, 1050, and 2055 manufactured by DIC Corporation, EPOTOTE YD-011, YD-013, YD-127, and YD-128 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., DER317, DER331, DER661, and DER664 manufactured by Dow Chemical Company, and Sumi-Epoxy ESA-011, ESA-014, ELA-115, and ELA-128 manufactured by Sumitomo Chemical Co., Ltd. (all trade names); jERYL903 manufactured by Mitsubishi Chemical Corporation, EPICLON 152, EPICLON 165, and NIPPON STEEL Chemical & Material Co., Ltd. Brominated epoxy resins such as EPOTOTE YDB-400 and YDB-500 manufactured by Dow Chemical Company, DER542 manufactured by Dow Chemical Company, and Sumi-Epoxy ESB-400 and ESB-700 manufactured by Sumitomo Chemical Co., Ltd. (all under the trade name); jER152 and jER154 manufactured by Mitsubishi Chemical Corporation, DEN431 and DEN438 manufactured by Dow Chemical Company, EPICLON N-730, EPICLON N-770, and EPICLON N-865 manufactured by DIC Corporation, EPOTOTE YDCN-701 and YDCN-704 manufactured by NIPPON STEEL Chemical & Material Co., Ltd., EPPN-201, EOCN-1025, EOCN-1020, EOCN-104S, RE-306, and NC-3000 manufactured by Nippon Kayaku Co., Ltd., and Sumi-Epoxy manufactured by Sumitomo Chemical Co., Ltd. ESCN-195X, ESCN-220, NIPPON STEEL Chemical & Material Co., Ltd.Novolac type epoxy resins such as YDCN-700-2, YDCN-700-3, YDCN-700-5, YDCN-700-7, YDCN-700-10, YDCN-704, and YDCN-704A manufactured by Nippon Paint Chemical Co., Ltd., and EPICLON N-680, N-690, and N-695 (all trade names) manufactured by DIC Corporation; EPICLON 830 manufactured by DIC Corporation, jER807 manufactured by Mitsubishi Chemical Corporation, bisphenol F type epoxy resins such as EPOTOTE YDF-170, YDF-175, and YDF-2004 (all trade names) manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Hydrogenated bisphenol A type epoxy resins such as ST-2004, ST-2007, ST-3000 (trade names), and YX8034 manufactured by Mitsubishi Chemical Corporation; jER604 manufactured by Mitsubishi Chemical Corporation, and NIPPON STEEL Chemical & Material Co., Ltd.glycidylamine type epoxy resins such as EPOTOTE YH-434 manufactured by Sumitomo Chemical Co., Ltd. and Sumi-Epoxy ELM-120 manufactured by Sumitomo Chemical Co., Ltd. (all trade names); hydantoin type epoxy resins; alicyclic epoxy resins such as CELLOXIDE 2021P manufactured by Daicel Corporation (trade name); trihydroxyphenylmethane type epoxy resins such as YL-933 manufactured by Mitsubishi Chemical Corporation and EPPN-501 and EPPN-502 manufactured by Nippon Kayaku Co., Ltd. (all trade names); bixylenol type or biphenol type epoxy resins or mixtures thereof such as YL-6056, YX-4000, and YL-6121 manufactured by Mitsubishi Chemical Corporation (all trade names); EBPS-200, ADEKA Bisphenol S type epoxy resins such as EPX-30 manufactured by CORPORATION and EXA-1514 (trade name) manufactured by DIC Corporation; bisphenol A novolac type epoxy resins such as jER157S (trade name) manufactured by Mitsubishi Chemical Corporation; tetraphenylolethane type epoxy resins such as jERYL-931 (trade name) manufactured by Mitsubishi Chemical Corporation; heterocyclic epoxy resins such as TEPIC (trade name) manufactured by Nissan Chemical Industries, Ltd.; diglycidyl phthalate resins such as BRENMAR DGT manufactured by NOF Corporation; tetraglycidyl xylenoylethane resins such as ZX-1063 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.; Examples of epoxy resins that contain a naphthalene skeleton include ESN-190 and ESN-360 manufactured by Nippon Steel Chemical & Material Co., Ltd., HP-4032, EXA-4750, and EXA-4700 manufactured by DIC Corporation, glycidyl methacrylate copolymer epoxy resins such as CP-50S and CP-50M manufactured by NOF Corporation, and further include cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resins, and CTBN-modified epoxy resins (e.g., YR-102 and YR-450 manufactured by Nippon Steel Chemical & Material Co., Ltd.), but are not limited thereto. These epoxy resins may be used alone or in combination of two or more.

[0069] The content of the (G) epoxy resin is preferably 10 to 100 parts by weight, more preferably 20 to 90 parts by weight, and even more preferably 30 to 80 parts by weight, per 100 parts by weight (solid content) of the (A) vinyl ester resin.

[0070] (H) Organic Solvent Regarding the organic solvent (H) used in the alkaline developing resin composition of the present invention, an organic solvent can be used for the purpose of synthesizing the vinyl ester resin (A), preparing the composition, or adjusting the viscosity when applying the composition to a substrate or a carrier film.

[0071] Examples of such organic solvents include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. The organic solvents described above can be used alone or as a mixture of two or more kinds.

[0072] When the alkaline development type resin composition of the present invention is used in forming a solder resist layer of a printed wiring board, the composition is adjusted to a viscosity suitable for the application method as necessary, and then applied to a printed wiring board on which a circuit has been formed in advance by a method such as screen printing, curtain coating, spray coating, or roll coating, and dried at a temperature of, for example, about 60 to 100 ° C. as necessary to form a tack-free coating film. Next, the composition is selectively exposed to active light through a photomask on which a predetermined exposure pattern has been formed, and the unexposed area is developed with an alkaline aqueous solution to form a resist pattern. Furthermore, by heating to a temperature of, for example, about 140 to 180 ° C. for thermal curing, the curing reaction of the epoxy resin (G) and the polymerization of the vinyl ester resin (A) can be promoted, and various properties such as adhesion, cold and heat shock resistance, heat resistance, solvent resistance, acid resistance, moisture absorption resistance, PCT resistance, adhesion, and electrical properties of the resulting resist film can be improved.

[0073] The alkaline aqueous solution used in the development may be an alkaline aqueous solution of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, etc. In addition, the irradiation light source used in the photocuring may be a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a semiconductor laser, a solid state laser, a xenon lamp, a metal halide lamp, etc. The alkaline developing resin composition of the present invention can be used in the form of a photocurable dry film obtained by applying the alkaline developing resin composition to a carrier film in advance and drying it, other than the method of applying the alkaline developing resin composition in liquid form directly to a substrate having a copper circuit. The case where the alkaline developing resin composition of the present invention is used as a photocurable dry film is shown below. The photocurable dry film has a structure in which a carrier film, a resin layer, and a peelable cover film used as required are laminated in this order. The resin layer is a layer obtained by applying the alkaline development type resin composition of the present invention to a carrier film and drying it. After forming the resin layer on the carrier film, a cover film is laminated on the resin layer to obtain a photocurable dry film. The carrier film is a thermoplastic film such as a polyester film having a thickness of 2 to 150 μm. The resin layer is formed by uniformly applying an alkaline developing resin composition to a carrier film with a thickness of 10 to 150 μm using a blade coater, lip coater, comma coater, film coater, or the like, and drying the composition. The cover film may be a polyethylene film, a polypropylene film, or the like, but it is preferable that the adhesive strength with the resin layer is smaller than that of the carrier film. The cured product of the present invention is obtained by applying an alkaline developable resin composition to copper and drying the resulting coating film, or by applying the alkaline developable resin composition to a carrier film, drying the resulting photocurable dry film, and laminating the resulting coating film on copper, followed by photocuring the resulting coating film. To prepare a cured product on a substrate having a copper circuit using a photocurable dry film, the cover film is peeled off, the resin layer and the substrate having a copper circuit are superimposed, and laminated using a laminator or the like to form a resin layer on the substrate having a copper circuit. The formed resin layer can be exposed to light, developed, and cured by heating in the same manner as above to form a cured product. The carrier film can be peeled off either before or after exposure. The alkaline developing resin composition is suitably used for forming a cured film on a printed wiring board, preferably a permanent insulating film, and particularly preferably a solder resist.

[0074] The present invention will be described in more detail with reference to examples and comparative examples, but the scope of the present invention and its embodiments are not limited thereto. "Parts" and "%" in the examples and comparative examples are by weight unless otherwise specified. The property values ​​of the composition of this example are tested by the method described below.

[0075] Synthesis Example In a four-neck flask equipped with a stirrer and a reflux condenser, 214 parts of cresol novolac epoxy resin EPICLON N-695 (DIC, epoxy equivalent = 214) were added, and 103 parts of diethylene glycol monoethyl ether acetate and 103 parts of a petroleum-based hydrocarbon solvent (Japan Energy Corporation, product name: Cactus Fines SF-01) were added and dissolved by heating. Next, 0.1 parts of hydroquinone as a polymerization inhibitor and 2.0 parts of triphenylphosphine as a reaction catalyst were added. This mixture was heated to 95-105°C, 72 parts of acrylic acid were slowly dropped, and the reaction was carried out for 16 hours. The obtained reaction product was cooled to 80-90°C, 91.2 parts of tetrahydrophthalic anhydride were added, the reaction was carried out for 8 hours, and the product was taken out after cooling. The carboxyl group-containing vinyl ester resin thus obtained had a non-volatile content of 65% and an acid value of the solid content of 87.5 mgKOH / g.

[0076] The vinyl ester resin solution (varnish) of the above synthesis example was used, and the components and ratios (parts by weight) shown in Table 1 were mixed and premixed with a stirrer, and then kneaded with a three-roll mill to prepare an alkaline developing resin composition. Furthermore, the adhesion and thermal shock resistance were evaluated by the following methods.

[0077] [Table 1]

[0078] A: Carboxyl group-containing vinyl ester resin of the synthesis example, solid content 65%, equivalent to the carboxyl group-containing vinyl ester resin of (5) F Pigment: Phthalocyanine Green, Pigment A manufactured by Dainippon Ink and Chemicals, Inc. F Defoamer: KS-66, manufactured by Shin-Etsu Chemical Co., Ltd. F Dispersant: BYK-110, polymerized phosphate ester, manufactured by BYK-Chemie B Photopolymerization initiator: Omnirad 369 E (chemical name: 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone), manufactured by IGM C Soft composite glass powder: K10, manufactured by Suzhou Kinyi New Materials Co., Ltd. (SiO2: 62.3-62.8%, Fe2O3: 0.0149-0.017%, Al2O3: 16.9-17.6%, CaO: 7.35-7.66%, MgO: 1.4-1.54%, B2O3: 9.6-10.3%) Mohs hardness: 5-6 E Talc: LMP-100, manufactured by FUJI TALC INDUSTRIAL Silica: A-8 Sibelco H Solvent: PGMEA, propylene glycol monomethyl ether 110 acetate G Epoxy resin: N-770-75EA, manufactured by DIC, novolac type multifunctional epoxy resin, solid content 75% D Compounds with two or more ethylenically unsaturated groups in one molecule: MT-3501G, manufactured by Zhangjiagang Dongya Di-Chi Biochemical Co., Ltd.

[0079] Performance evaluation (1) Adhesion (Pull off test) The alkaline development type resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80° C. for 30 minutes. After cooling to room temperature, the coating was exposed to 300 mJ / cm 2 using an exposure device equipped with a high-pressure mercury lamp. 2 Then, the resist was developed with a 1 wt% aqueous sodium carbonate solution at a pressure of 0.2 MPa and a liquid temperature of 30°C for 60 seconds, and then cured in a hot air circulation drying oven at 150°C for 60 minutes. In this way, a copper circuit board having a cured film was produced. A DeFelsko PosiTest AT digital display pull-off adhesion tester (capable of measuring the adhesion of coatings on metal, concrete, and other materials) was also prepared. A dolly (dimensions: bottom diameter 1 cm) was attached and fixed (heated at 120°C for 1 hour) to the surface of the cured film (as shown in the image in Figure 3, for example) using an Emerson & Cumming adhesive (LOCTITE ABLESTIK 2332-17 high strength structural adhesive), and the tensile force required to separate the cured film from the copper substrate per unit area was measured, expressed in MPa, according to ATSM D4541. ○: Tensile strength is 6.0 MPa or more. ×: Tensile strength is less than 6.0 MPa.

[0080] (2) Thermal shock resistance The alkaline development type resin compositions of the Examples and Comparative Examples were applied to the entire surface of a substrate on which a 2 mm copper wire pattern had been formed by screen printing so as to have a thickness of 40 μm, and dried in a hot air circulation drying oven at 80° C. for 30 minutes. After cooling to room temperature, the coating was exposed to 400 mJ / cm 2 using an exposure device equipped with a high-pressure mercury lamp. 2 Then, the resist was developed with a 1 wt% aqueous sodium carbonate solution at a pressure of 0.2 MPa and a liquid temperature of 30°C for 60 seconds, and then cured in a hot air circulation drying oven at 150°C for 60 minutes. The cumulative exposure in the UV transfer oven was 2000 mJ / cm 2 By irradiating ultraviolet rays under the above conditions, 17 evaluation boards having a right-angled resist pattern were fabricated for crack resistance during thermal cycles. The evaluation boards fabricated as described above were placed in a temperature cycler that performs thermal cycles at -40°C to 160°C, and a thermal shock cycle test (TCT test) was performed by setting different cycle numbers. Next, the appearance was observed for each number of cycles, and the maximum number of cycles at which cracks did not occur was recorded (see Figures 1 and 2 for the presence or absence of cracks), and the evaluation criteria are shown below. ◯: No cracks were observed even after 1000 or more cycles. △: No cracks were generated after 700 or more and less than 1000 cycles. ×: Cracks occurred within 700 cycles.

[0081] As can be seen from the above, by adjusting the composition to that of Examples 1 to 3, an alkaline development type resin composition capable of obtaining a solder resist layer excellent in both thermal shock resistance and adhesion can be obtained. In contrast, in Comparative Examples 1 and 2, only talc and silica were used as fillers, so adhesion was low, and in Comparative Example 2, in which the amount of talc used was even less, thermal shock resistance was also reduced. In Comparative Example 3, only soft composite glass powder was used, and adhesion was improved, but thermal shock resistance was low. In Comparative Example 4, only silica was used, and adhesion was similarly improved, but thermal shock resistance was low. In Comparative Example 5, soft composite glass powder and silica were used in combination, and adhesion was similarly improved, but thermal shock resistance was low.

Claims

1. (A) a vinyl ester resin, (B) a photopolymerization initiator, (C) a glass powder, (D) a compound having two or more ethylenically unsaturated groups in one molecule, and (E) an inorganic filler, the (E) inorganic filler including talc; The glass powder (C) contains, in weight percent, SiO 2 :60~65%, Fe 2 O 3 :0.01~0.02%, Al 2 O 3 :14-20%, CaO: 6-9%, MgO: 1-2%, B 2 O 3 8 to 12% of the glass powder (C), and the Mohs hardness of the glass powder (C) is less than 6.

5.

2. 2. The alkaline developing resin composition according to claim 1, further comprising (F) another additive other than (B) the photopolymerization initiator and (C) the glass powder.

3. 3. The alkaline developing resin composition according to claim 1, further comprising an epoxy resin (G).

4. 3. The alkaline developing resin composition according to claim 1, further comprising (H) an organic solvent.

5. 4. The alkaline developing resin composition according to claim 3, further comprising (H) an organic solvent.

6. 6. A photocurable dry film obtained by applying the alkaline developing resin composition according to claim 1 to a carrier film and drying the applied resin composition.

7. A coating film obtained by applying the alkaline developable resin composition according to any one of claims 1 to 5 to copper and drying the composition, or a cured product obtained by applying the alkaline developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on copper, and photocuring the resulting coating film.

8. A printed wiring board comprising: a coating film obtained by applying the alkaline developable resin composition according to any one of claims 1 to 5 to a substrate having a copper circuit and drying the composition; or a cured product obtained by applying the alkaline developable resin composition to a carrier film, drying the composition, laminating the resulting photocurable dry film on a substrate having a copper circuit, photocuring the coating film, and then thermally curing the resulting cured product.

Citation Information

Patent Citations

  • A photosensitive resin composition, a two-pack type photosensitive resin composition, a dry film, and a printed wiring board

    CN110320752A

  • Photosensitive paste, member for display, and display

    JP2002082433A

  • Resin composition for solder resist, resin composition for marking ink, hardened material, and printed wiring board

    JP2015170797A

  • A photosensitive paste composition, a barrier ribprepared using the composition and a plasma displaypanel comprising the barrier rib

    KR100787450B1

  • Photosensitive resin composition, photosensitive resin sheet, cured product, hollow structure, electronic component, and elastic wave filter

    WO2022163610A1